2009
DOI: 10.1063/1.3264961
|View full text |Cite
|
Sign up to set email alerts
|

High electron mobility and low sheet resistance in lattice-matched AlInN/AlN/GaN/AlN/GaN double-channel heterostructure

Abstract: High electron mobility and low sheet resistance were achieved in lattice-matched AlInN/AlN/GaN/AlN/GaN double-channel (DC) heterostructure. Two-dimensional electron gas (2DEG) of the DC heterostructure was divided into the double channels and the room-temperature mobility was increased to 1430 cm2/V s by reducing the 2DEG density in each channel, compared with low electron mobility (1090 cm2/V s) for lattice-matched AlInN/AlN/GaN single-channel heterostructure. It was found that the 2DEG mobility was limited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…buffer layer, a thin AlN interlayer, and 7-nm InAlN terminal barrier layer [5,6]. The aluminum composition of InAlN layer was characterized by high resolution X-ray diffraction (HR-XRD), and its value was about 83%.…”
Section: Methodsmentioning
confidence: 99%
“…buffer layer, a thin AlN interlayer, and 7-nm InAlN terminal barrier layer [5,6]. The aluminum composition of InAlN layer was characterized by high resolution X-ray diffraction (HR-XRD), and its value was about 83%.…”
Section: Methodsmentioning
confidence: 99%
“…AlGaN-GaN HEMTs can be used for high-power applications because they produce an intense output density compared with conventional AlGaAs-GaAs HEMTs. [15][16][17] The advantages of nitride semiconductors over other III-V semiconductors are the large band offset between GaN and Al x Ga (1Àx) N, the large LOphonon energy, and the large electron effective mass. All the above-mentioned properties have significant effects on the electronic transport because they shorten the wavelength and relaxation time, which is required for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have appeared in the literature. Zhang et al [17,18] reported a double channel (DC) AlInN/GaN heterostructure with high electron mobility and low sheet resistance compared to a single channel (SC). They reported higher RT electron mobility (1570 cm 2 /Vs) along with lower sheet resistance (222 Ω/sq) in AlInN/GaN DC compared to an AlInN/ GaN SC heterostructure [17].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [17,18] reported a double channel (DC) AlInN/GaN heterostructure with high electron mobility and low sheet resistance compared to a single channel (SC). They reported higher RT electron mobility (1570 cm 2 /Vs) along with lower sheet resistance (222 Ω/sq) in AlInN/GaN DC compared to an AlInN/ GaN SC heterostructure [17]. The same group [18] investigated the effect of distance between dual channel (d 1 ) and the thickness of the bottom AlN insert layer (d 2 ) on the transport properties of AlInN/GaN DC HEMTs.…”
Section: Introductionmentioning
confidence: 99%